Laboratory test results of serum and cerebrospinal fluid in patients with neurosyphilis and their diagnostic value - GAO Pingping; ZHANG Xiaolong; SUN Zhe; ZHANG Ran; WANG Jing (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To analyze the laboratory test results of serum and cerebrospinal fluid (CSF) in patients with neurosyphilis (NS) and explore the risk factors for the onset of NS and their diagnostic value. [Methods] A retrospective analysis was conducted on 264 syphilis patients admitted to the First Affiliated Hospital and the Second Affiliated Hospital of Anhui Medical University from August 2020 to August 2024. The patients were divided into two groups: NS group (n=80) and non-NS group (n=184). Comparative analysis was performed on gender, age, and laboratory test results of serum and CSF. Statistical analysis was conducted using SPSS software, with multivariate logistic regression analysis and predictive accuracy assessment applied to factors showing significant differences in univariate analysis. [Results] Compared with the non-NS group, the NS group had a higher proportion of males, older age, elevated blood glucose, and increased serum levels of ALT, total bilirubin, and creatinine. Although serum levels of ALT, total bilirubin, and creatinine were increased, they generally fluctuated within the normal reference range. Significant (P<0.05) were observed in CSF parameters, including TPPA positivity rate, TRUST positivity rate, albumin, white blood cell count, IgG, Pandy's test positivity rate, and albumin quotient. Multivariate logistic regression analysis revealed that age, blood glucose, CSF albumin, white blood cell count, IgG, Pandy's test positivity, and albumin quotient were statistically significant (P<0.05). ROC curve analysis of these risk factors showed that CSF albumin, white blood cell count, IgG, and albumin quotient had higher AUC and sensitivity values. [Conclusions] Male patients, older age, and increased blood glucose levels are associated with a higher risk of developing NS. CSF albumin, white blood cell count, IgG, Pandy's test positivity, and albumin quotient can improve the diagnostic accuracy of NS, with CSF IgG demonstrating the highest diagnostic sensitivity. Early CSF puncture examination is recommended for timely detection and treatment of neurosyphilis.